Electrophoretic mobility of Tween 80-encapsulated agarwood oil in aqueous - Boon, Yih Tien; Naim, Mohd Nazli; Zakaria, Rabitah; Abu Bakar, Noor Fitrah; Ahmad, Noraini (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
A study on the feasibility of using gel electrophoresis technique in grading the agarwood oil quality was investigated. Prior to electrophoresis, the emulsified agarwood oil droplets were screened by a diffuse layer of ions that have equal absolute charge to that of the droplets surface charge in aqueous phase. The condition was obtained by varying the concentrations of non-ionic surfactant; Tween 80 until the critical aggregation concentration (CAC) value of 0.0167% (v/v) was achieved. The prepared droplets suspended in the aqueous within nano-metre size and had ability to migrate through the agarose gel with its own specific electrophoretic mobility. However, due to the limitation of gel pore size, only large oil droplets (>200 nm) indicated visible bands. Overall, a novel work for grading the emulsified agarwood oil droplet with its own electrical properties was feasible.